Pengaruh Perputaran Kas dan Perputaran Piutang terhadap Likuiditas Perusahaan Manufaktur Sektor Industri Makanan dan Minuman yang Terdaftar di BEI Tahun 2020-2022 - Sari, Rina; Wirananda, Henny Andriyani (Jurnal EMT KITA, 2025)
The aim of this research is to determine the partial and simultaneous influence of cash turnover and receivables turnover on liquidity in food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. This research is quantitative research. The research sample used a purposive sampling method with a total of 30 samples. This research data analysis technique uses classical assumption testing methods, multiple linear regression analysis, and hypothesis testing. The results of the partial test value of cash turnover tcount 1.825 > ttable 1.703 significance 0.002 < 0.05. Partial test value of receivables turnover tcount 3.730 < ttable 1.703 significance 0.001 < 0.05 Simultaneously Fcount value 9.373 > Ftable 3.35 significance 0.000 < 0.05. The conclusion of the analysis results shows that cash turnover and receivables turnover partially and significantly influence the company's liquidity. Cash turnover and receivables turnover simultaneously and significantly influence the company's liquidity.